MOBILE APPLICATION FOR AUTISM SPECTRUM DISORDER CHILDREN - MERYEM, ARIOUA; RAWYA, CHENNI; Supervisor :GHRIBI, HAYAT (University of M'sila, 2023)
The objective of this dissertation is to create a mobile application that helps autistic children express their feelings and understand the feelings of others. We decided to work on the point of expressing feelings, so we proposed the idea of creating an application to be a tool to help the supervisor educating the autistic child to express his feelings. And it is approved by the specialists, and because the autistic child cannot use the phone or the smart devices, we relied on the supervisor to help him. We have followed the steps and advice imposed by the specialists to create it. We introduced first some theoretical concepts, about autism, as well as the contribution of technology in helping this group and then we used the UML modeling method to describe the main features and advantages of our project. Finally, we have reached the realization phase where we used integrated developing environments, which are android studio, and Google Firebase services for the database implementation, And also Adobe Illustrator to draw faces and scenes of expression these tools made the development easier, and we concluded the dissertation with screenshots of some interfaces from our application.
Keywords: Android, UML, Firebase, Mobile application, Adobe Illustrator, Express feelings.